2009
DOI: 10.1111/j.1468-1331.2009.02640.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and cognitive impairment amongst elderly people in Chinese population: a cross‐sectional study

Abstract: MetS is associated with cognitive impairment amongst elderly people in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
4
12
2
Order By: Relevance
“…Surprisingly, other factors such as hyperglycaemia and hypertension were not statistically associated with cognitive impairment in our study. These results contradict some previous studies [6, 24], specifically the study performed by Friedman et al, who found that hypertension increased the risk for cognitive impairment [13]. One explanation could be the differences between populations, especially the relatively young average age in our study (36.6 years) compared with previous studies (47.3 years in Friedman's study).…”
Section: Discussioncontrasting
confidence: 99%
“…Surprisingly, other factors such as hyperglycaemia and hypertension were not statistically associated with cognitive impairment in our study. These results contradict some previous studies [6, 24], specifically the study performed by Friedman et al, who found that hypertension increased the risk for cognitive impairment [13]. One explanation could be the differences between populations, especially the relatively young average age in our study (36.6 years) compared with previous studies (47.3 years in Friedman's study).…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings showed similar results and magnitude confirming previous studies of the association between MetS and lower cognitive performance [21][22][23][24] , and extend these findings to a predominantly Hispanic population in which the MetS prevalence is high. Hispanics have been traditionally understudied, although they are the fastest growing population in the US, they have the highest MetS prevalence, and together with non-Hispanic blacks, may be at a higher risk of dementia than non-Hispanic whites [25] .…”
Section: Discussionsupporting
confidence: 81%
“…Our findings add to a growing body of evidence that suggests MetS is associated with accelerated cognitive aging and the risk of cognitive impairment in acute cerebral ischemia patients, independently of other known risk factors for cognitive impairment (OR 3.542; 95% CI:1.972–6.361, Table 4). This correlation is consistent with the findings of other studies in Chinese populations [5, 6, 24]. However, the overall prevalence of MetS in the present study was 39.3%, which differed from values reported for other Chinese population-based studies [5, 6, 24].…”
Section: Discussionsupporting
confidence: 90%
“…This correlation is consistent with the findings of other studies in Chinese populations [5, 6, 24]. However, the overall prevalence of MetS in the present study was 39.3%, which differed from values reported for other Chinese population-based studies [5, 6, 24]. This discrepancy may be explained by differences in the characteristics of the study populations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation